Gender Analysis Organizational Culture Of Educational Institutions : Study at the Faculty of Ushuluddin, Adab, and Humanities IAIN Purwokerto - Maftuchah, Farichahtul; Waliko, Waliko (DAS Institute, 2022)
Background of this study: The reality of gender differences turns out to cause various forms of injustice in one sex. For this reason, efforts are needed to strengthen the structure in fostering gender justice. Educational institutions are strategic elements that are able to transfer the values of gender to members of the organization. This research is qualitative research with methods of collecting interview data, observation and documentation. The results showed the organizational culture of IAIN Purwokerto faculty (FUAH) can be mapped across three categories: gender responsive, gender neutral and gender bias. The gender responsive category is in the aspect of the lecture process, where most lecturers treat students equally and provide motivation and support for those who are left behind. For gender neutral categories there are aspects of mission vision, leadership, awarding mechanisms, appointments, all of which are based on applicable rules. The appointment of officials and the awarding of awards and opportunities to both lecturers, education personnel, and students are not based on gender, but rather based on predetermined criteria and qualifications. For the gender bias category there is in the aspect of infrastructure facilities, which include public facilities (stairs), seating for students in the lecture hall, and toilets.